DECOMPOSITION OF BOCR â€œ ARISAN MAJELIS TAâ€™LIMâ€AS SUPPORT PROGRAM FOR MICRO SYARIAH FINANCIAL INSTITUTION, CASE STUDY OF BOGOR CITY - Afriadi, Fiqih (EAJ (Economic and Accounting Journal), 2018)
The purpose of this research is to uncover the uniqueness of Beneffit, Opportunity, Cost and Risk (BOCR) from arisan majelis taâ€™lim in supporting the sustainability of Sharia Micro Financial Institution (SMFI). Benefit and Opportunity need to be known as the positive side of the arisan majelis taâ€™lim in SMFI, while the Cost and Risk needs to be known to see the negative side. To reveal the uniqueness of BOCR methodology is done byusing the methodology of ANP BOCR problem decomposition.  Decomposition of the problem is done by surveying to arisan majelis taâ€™lim in Bogor city and also indepth interview to practitioners of arisan majelis taâ€™lim and SMFI practitioners. The result of the research shows several Benefits that can be obtained include; increase the number of members, high social capital honesty and integrity typical of â€œwong cilikâ€ , and low  cost. For Opportunity that can be obtained that is; savings fund opportunities, poor empowerment opportunities, microfinance opportunities, and opportunities for increased financing returns. The various costs that must be in the responsibility is; operational costs,empowerment costs, product development costs, and socialization and education costs. While some risks that need to be the attention that is; credit risk, sharia compliance risk, operational risk, and social risk.